Evaluation of postmenopausal bleeding: a cross sectional study - Paul, Papiya; Devi, Rajkumari Praneshwari; Kom, Telen Thangkhojam; Nath, Priyanka; Devi, Thoudam Neesha; Longjam, Nirmala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Postmenopausal bleeding (PMB) is one of the most common reasons for referral to tertiary care centres with a strong suspicion of malignancy. Endometrial cancer is the most common cause of gynaecological malignancy in the West, but in India the incidence rates are low. Eighty to ninety percent (80-90%) women have benign conditions in India. The aim and objectives of my study are to evaluate causes of PMB and sociodemographic characteristics among postmenopausal women. Methods: A hospital based analytical cross-sectional study was conducted among women above 45 years with PMB admitted in the department of obstetrics and gynaecology, regional institute of medical sciences (RIMS), Imphal. The study was conducted for a period of two years from October 2019 to September 2021. Results: In this study, out of 50 postmenopausal women 35 (70%) belong to age group >50 years and only 15 (30%) belong to age group <50 years. The most common cause of PMB in this study was found to be endometrial atrophy (12 out of 50) and two thirds of them having ET between 2-4 mm. This association is found to be statistically significant. The incidence of genital tract malignancy in our study is 14%. Incidence of endometrial carcinoma (8%) is slightly higher than cervical cancer (6%). The incidence of premalignant lesions (endometrial hyperplasia with atypia, endometrial intraepithelial neoplasia, cervical intraepithelial neoplasia) is 20% in this study. The study did not show significant association of clinical variables with benign, premalignant or malignant causes of PMB. Conclusions: With increase in life expectancy the incidence of PMB is expected to increase in future. Since the incidence of malignancy is quite high, any bleeding in that age group should be evaluated in the line of malignancy unless proved to be otherwise.